Dual‐Modal Magnetic Resonance/Fluorescent Zinc Probes for Pancreatic β‐Cell Mass Imaging. Issue 13 (3rd March 2015) - Stasiuk, Graeme J.; Minuzzi, Florencia; Sae‐Heng, Myra; Rivas, Charlotte; Juretschke, Hans‐Paul; Piemonti, Lorenzo; Allegrini, Peter R.; Laurent, Didier; Duckworth, Andrew R.; Beeby, Andrew; Rutter, Guy A.; Long, Nicholas J.
Abstract Despite the contribution of changes in pancreatic β‐cell mass to the development of all forms of diabetes mellitus, few robust approaches currently exist to monitor these changes prospectively in vivo. Although magnetic‐resonance imaging (MRI) provides a potentially useful technique, targeting MRI‐active probes to the β cell has proved challenging. Zinc ions are highly concentrated in the secretory granule, but they are relatively less abundant in the exocrine pancreas and in other tissues. We have therefore developed functional dual‐modal probes based on transition‐metal chelates capable of binding zinc. The first of these, Gd⋅1, binds ZnII directly by means of an amidoquinoline moiety (AQA), thus causing a large ratiometric Stokes shift in the fluorescence from λem=410 to 500 nm with an increase in relaxivity from r1=4.2 up to 4.9 mM−1 s−1. The probe is efficiently accumulated into secretory granules in β‐cell‐derived lines and isolated islets, but more poorly by non‐endocrine cells, and leads to a reduction in T1 in human islets. In vivo murine studies of Gd⋅1 have shown accumulation of the probe in the pancreas with increased signal intensity over 140 minutes.